ANALISIS KETERBUKAAN DOKUMEN REKAM MEDIS PASIEN COVID-19 DALAM MENDUKUNG DATA RISET KESEHATAN (STUDI LITERATUR) - Amri Hariri (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The medical record document (DRM) of COVID-19 patients is public information of a special nature. The openness of DRM for COVID-19 patients in supporting health data research is very important in the future. This study aims to determine the medical record documents in guaranteeing the identity of COVID-19 patients, as well as to describe the impact of DRM on COVID-19 patients in supporting health data research. The method of this research is qualitative with a literature study approach. Scientific literature searches are carried out through the help of a web-based paper link system. The results of this study suggest that DRM for COVID-19 patients used for health research data needs can be carried out by considering the rights of patients, medical staff, and hospitals by applicable legal provisions. Furthermore, researchers must involve the Health Research Ethics Commission (KEPK) to conduct ethical studies on health research. The impact of medical access for COVID-19 patients on the quality of health care and services, increasing public knowledge in dealing with future pandemics, and new knowledge of health in the world.